Cellulose Nanofibers Improve the Performance of Retrograded Starch/Pectin Microparticles for Colon-Specific Delivery of 5-ASA - Andréia Bagliotti Meneguin; Rafael Miguel Sábio; Maurício Palmeira Chaves de Souza; Richard Perosa Fernandes; Anselmo Gomes de Oliveira; Marlus Chorilli (MDPI AG, 2021)
Cellulose nanofibers (CNF) were employed as the nanoreinforcement of a retrograded starch/pectin (RS/P) excipient to optimize its colon-specific properties. Although starch retrogradation ranged from 32 to 73%, CNF addition discretely disfavored the RS yield. This result agrees with the finding that in situ CNF reduces the presence of the RS crystallinity pattern. A thermal analysis revealed that the contribution of pectin improves the thermal stability of the RS/CNF mixture. Through a complete factorial design, it was possible to optimize the spray-drying conditions to obtain powders with high yield (57%) and low moisture content (1.2%). The powders observed by Field Emission Gum Scanning Electron Microscopy (FEG-SEM) had 1-10 µm and a circular shape. The developed methodology allowed us to obtain 5-aminosalicilic acid-loaded microparticles with high encapsulation efficiency (16-98%) and drug loading (1.97-26.63%). The presence of CNF in RS/P samples was responsible for decreasing the burst effect of release in simulated gastric and duodenal media, allowing the greatest mass of drug to be targeted to the colon. Considering that spray-drying is a scalable process, widely used by the pharmaceutical industry, the results obtained indicate the potential of these microparticles as raw material for obtaining other dosage forms to deliver 5-ASA to the distal parts of gastrointestinal tract, affected by inflammatory bowel disease.